2022
DOI: 10.3390/cells11172689
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cells: Global Number, Density and Vulnerability to Glaucomatous Injury in Common Laboratory Mice

Abstract: How many RBPMS+ retinal ganglion cells (RGCs) does a standard C57BL/6 laboratory mouse have on average and is this number substrain- or sex-dependent? Do RGCs of (European) C57BL/6J and -N mice show a different intrinsic vulnerability upon glaucomatous injury? Global RGC numbers and densities of common laboratory mice were previously determined via axon counts, retrograde tracing or BRN3A immunohistochemistry. Here, we report the global RGC number and density by exploiting the freely available tool RGCode to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The degree of cumulative IOP elevation and the eventual RGC density reduction rate both occurred in the present study and were comparable with previously reported results [14‒17]. The comparable RGC density in WT and Aqp9 KO mice at baseline replicated our previous report [3], supporting that Aqp9 gene deletion alone does not induce RGC death under physiological conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The degree of cumulative IOP elevation and the eventual RGC density reduction rate both occurred in the present study and were comparable with previously reported results [14‒17]. The comparable RGC density in WT and Aqp9 KO mice at baseline replicated our previous report [3], supporting that Aqp9 gene deletion alone does not induce RGC death under physiological conditions.…”
Section: Discussionsupporting
confidence: 93%
“…The mouse model of chronic ocular hypertension by MB injection into the anterior chamber was partially modified from previous reports [14][15][16]. Mice were anesthetized with intraperitoneal administration of a ketamine (100 mg/kg) and xylazine (10 mg/kg) mixture, and the pupil of the left eye was pharmacologically dilated with 0.5% tropicamide and 0.5% phenylephrine hydrochloride mixed ophthalmic solution (Santen Pharmaceutical Co., Osaka, Japan).…”
Section: Mb Injection Into Anterior Chambermentioning
confidence: 99%
“…In experiments estimating RGC numbers across the entire mouse retina, it has been determined that Brn3a staining may miss about 2000 to 6000 RGCs, because the total number of RGCs in C57BL/6 mouse retina has been estimated to be between 40,000 and 60,000 cells. 30 Whether or not this affects the ability of an experiment to detect significant changes will ultimately depend on the goal of each study.…”
Section: Discussionmentioning
confidence: 99%
“…Various algorithms have also been developed to perform automatic counting of RGCs, although some may still require manually adjusting some parameters. 10 , 30 Whereas preferred in many experiments, particularly where staining is ideal, it is also recognized that often in diseased retinas or other situations where staining is less clear, automated counting may introduce more variability than manual counting. 11 Thus, by design, the current studies evaluated staining in a commonly used manual counting method.…”
Section: Discussionmentioning
confidence: 99%
“…We previously generated a cellular atlas of mouse RGC types by scRNA-seq, identifying 46 types [11][12][13] . Since RGCs account for <1% of all retinal cells, our previous experiments pooled RGCs from ~6-8 retinas for each scRNA-seq collection, preventing the assessment of sample-specific gene expression 12,[14][15][16] . In this study, we tagged RGCs from individual retinas using cholesterolmodified oligos (CMOs), which utilize a barcode attached to a lipid scaffold that can conjugate to cell surfaces 7 .…”
Section: Introductionmentioning
confidence: 99%